2019
DOI: 10.1021/acs.jpcc.9b01199
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Properties from Both the Bulk and Surface of Iron Silicides: A Unified Theoretical Study

Abstract: The properties from both bulk phases (magnetism and thermal stability) and surface (composition, orientation, and stability) of iron silicide model compounds were evaluated by a theoretical study with a combination of density functional theory, ab initio atomistic thermodynamics, and Wulff construction. Magnetism, one of the properties originated from bulk phases, has been chosen as an example to demonstrate how to correlate it with the local chemical environment to provide an in-depth understanding. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Four 2D FeSi x alloys are FM at their ground state with the energy difference between AFM and FM varying from 143.04 to 546.51 meV/Fe, similar to previously reported FM Fe 2 Si (205 meV/Fe) and FeSi 2 (36 meV/Fe), , suggesting that the FM ground state is solid for 2D FeSi x alloys, which is independent of the value of x in the current study. Additionally, for Fe 3 Si 2 , Fe 4 Si 2 -hex, and Fe 4 Si 2 -orth, the FM ground state is consistent with their bulk counterparts, while 2D FeSi 2 exhibits ferromagnetism different from its nonmagnetic bulk counterpart after dimensional reduction …”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Four 2D FeSi x alloys are FM at their ground state with the energy difference between AFM and FM varying from 143.04 to 546.51 meV/Fe, similar to previously reported FM Fe 2 Si (205 meV/Fe) and FeSi 2 (36 meV/Fe), , suggesting that the FM ground state is solid for 2D FeSi x alloys, which is independent of the value of x in the current study. Additionally, for Fe 3 Si 2 , Fe 4 Si 2 -hex, and Fe 4 Si 2 -orth, the FM ground state is consistent with their bulk counterparts, while 2D FeSi 2 exhibits ferromagnetism different from its nonmagnetic bulk counterpart after dimensional reduction …”
mentioning
confidence: 57%
“…Additionally, for Fe 3 Si 2 , Fe 4 Si 2 -hex, and Fe 4 Si 2 -orth, the FM ground state is consistent with their bulk counterparts, while 2D FeSi 2 exhibits ferromagnetism different from its nonmagnetic bulk counterpart after dimensional reduction. 44 Next, the calculated electronic band structures and density of states (DOS) projected on the atomic orbital of 2D FeSi x alloys at their FM ground states with the screened hybrid HSE06 functionals are plotted in Figure 3a− S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we investigate the magnetic response of iron disilicide nanocrystals that are embedded in a Si electrode upon its electrochemical lithiation and delithiation of the latter. In the bulk, the stable semiconducting β-FeSi 2 and the metastable metallic α-FeSi 2 phase are both paramagnetic [26]. However, it has been shown that ferromagnetism or superparamagnetism can occur in iron disilicide nanostructures, which has been attributed to lattice distortions and/or chemical disorder at the surface, leading locally to magnetic Fe-rich defective regions [27][28][29][30][31].…”
mentioning
confidence: 99%